Collectively figuring it out : foreign-trained health professionals and labor market integration - Caidi, Nadia (2021)
Background. Foreign-trained health professionals arrive in the United States and Canada to find a professional environment that is often unwelcoming and complex. Objectives. We examine the nature of information in foreign-trained health professionals’ lives as they attempt to integrate into the North American labor market. We focus on the role that online discussion forums play in channeling the discussions: what functions do these online spaces support (e.g., informational, emotional, instrumental and phatic) and how information is shared (e.g., sharing stories, linking to/reposting resources, contextualizing and critiquing). Methods. Content analysis was carried out on a sample of postings directed at foreign-trained health professionals in five online forums: AllNurses and Trackitt in the United States; and Canadian Desi, LoonLounge and CanadaVisa in Canada. Results. The interactions in these forums include requesting guidance and clarification about the North American system, sharing experiences and stories, expressing visceral or affective reactions, offering opinions, and negotiating the norms and etiquette of the forum. The content of the postings mostly revolve around issues relating to the immigration process, certification and employability. Other issues identified can be grouped into three categories: information preparedness, information as support and informational practices. Conclusion. Foreign-trained health professionals are faced with a combination of unfamiliar healthcare system, terminology, information sources and information-seeking practices. Online communities supported by online discussion forums help these health professionals integrate into the local healthcare system.